The mineralogical and geochemical composition of Holocene sediments from Lake Hazar, Elazig, Eastern Turkey: implications for weathering, paleoclimate, redox conditions, provenance, and tectonic setting - Bal Akkoca, Dicle; Eris, K. Kadir; Cagatay, M. Namik; Biltekin, Demet (Tubitak Scientific & Technological Research Council Turkey, 2019)
Mineralogical and geochemical analyses of samples collected from piston core HZ11-P01 at the western margin of Lake Hazar were studied to determine the provenance and weathering conditions on the source area together with tectonic setting of the source rocks, paleoclimate of the region, and paleo-redox conditions of the lake sediments. Nonclay minerals in the sediment core are represented by feldspar, quartz, dolomite, and calcite. The clay mineral assemblage consists of smectite/chlorite mixed-layer clay, chlorite, and illite. Most major, trace, and rare earth element contents of the lake samples are generally similar to those of the catchment area. Chondrite-normalized rare earth element patterns of the lake samples are characterized by enrichment of light rare earth elements, a relatively flat heavy rare earth element pattern, and no Eu negative anomaly. The chemical index of alteration and index of compositional variability of the core sediment suggested that the intensity of weathering in the source area was low to moderate. The paleoclimatic indicator (C-values) showed that a paleoclimate changing from semiarid to semimoist prevailed during the last similar to 2 ka BP. Authigenic U and element ratios such as Th/U, Ni/Co, Cu/Zn, V/Cr, Eu/Eu*, and Ce/Ce* indicate that the lake sediments were deposited under oxic conditions. La/Sc, Co/ th, Cr/Th, Zr/Sc, and Th/Sc element ratios in the core sediments are consistent with values of sediments derived from mainly mafic and intermediate source rocks. According to discriminant-function diagrams, lake samples are plotted within the arc setting and arc-continent collision, which is in accordance with the geology of the study area.
Keywords: Chemical index of alteration; redox conditions; provenance; tectonic setting; Lake Hazar; Eastern Turkey